In-vitro bioactivity, biocompatibility and dissolution studies of diopside prepared from biowaste by using sol–gel combustion method - Choudhary, R.; Vecstaudza, J.; Krishnamurithy, G.; Raghavendran, Hanumanth Rao Balaji; Murali, M.R.; Kamarul, Tunku; Swamiappan, S.; Locs, J. (Elsevier, 2016)
Diopside was synthesized from biowaste (Eggshell) by sol–gel combustion method at low calcination temperature and the influence of two different fuels (urea, l-alanine) on the phase formation temperature, physical and biological properties of the resultant diopside was studied. The synthesized materials were characterized by heating microscopy, FTIR, XRD, BET, SEM and EDAX techniques. BET analysis reveals particles were of submicron size with porosity in the nanometer range. Bone-like apatite deposition ability of diopside scaffolds was examined under static and circulation mode of SBF (Simulated Body Fluid). It was noticed that diopside has the capability to deposit HAP (hydroxyapatite) within the early stages of immersion. ICP-OES analysis indicates release of Ca, Mg, Si ions and removal of P ions from the SBF, but in different quantities from diopside scaffolds. Cytocompatability studies on human bone marrow stromal cells (hBMSCs) revealed good cellular attachment on the surface of diopside scaffolds and formation of extracellular matrix (ECM). This study suggests that the usage of eggshell biowaste as calcium source provides an effective substitute for synthetic starting materials to fabricate bioproducts for biomedical applications.